Teriparatide therapy in joint replacement surgery: mitigating complications and improving patient outcomes in osteoarthritis - Chaudhari, Yogesh (International Journal of Research in Orthopaedics, 2023)
Background: Teriparatide, a synthetic form of parathyroid hormone, has gained significant recognition as an effective treatment for osteoporosis. Its ability to stimulate bone formation and improve bone mineral density has made it a valuable therapeutic option in managing this prevalent skeletal disorder. However, its safety and potential benefits in preventing bone mineral density (BMD) loss after joint replacement surgery and post-surgical complications have yet to be extensively investigated. Methods: This retrospective study included 32 patients who received teriparatide following joint replacement surgery for osteoarthritis. The analysis focused on assessing teriparatide’s effectiveness in any reductions in post-surgical complications and adverse events, if any. Results: No teriparatide-related adverse events and post-surgical complications were reported during the follow-ups and the entire study duration. Conclusions: Teriparatide demonstrated effectiveness in joint replacement patients. Further research is needed to explore long-term benefits and effects on implant longevity.